TOC - Emerging Technology, International Journal of Engineering and (International Journal of Engineering and Emerging Technology; Vol 5 No 1 (2020): January - JuneDO - 10.24843/IJEET.2020.v05.i01.p01, 2020)
TOC International Journal of Engineering And Emerging Technology  | A Publication Of The Doctorate Program Of Engineering Science Udayana University | January - June 2020 | Volume 5 Number 1